(untitled) (Scientia Agropecuaria, 2023)
It is important to identify the emotional response and sensorial needs of consumers to get commercial success of the alimentary sector in order to improve the consumption experience. Obtaining attractive characteristics through the application of the Kano model allows increase the consumer satisfaction. Furthermore, the Napping®-Ultra Flash Profile (UFP) methodology makes it possible that producers of craft beers may well reliably characterize their products. Likewise, the use of External Preference Mapping (EPM) allows the identification of those highly accepted products. In this sense, the goal of the present study was to validate, through the application of EPM, that the incorporation of the Kano model in the sensory design increases consumer satisfaction in turn obtaining the sensory profile of Peruvian craft beers. The Kano model permitted to determine the attractive characteristics of representative craft beers of the Lima market: the presence of exotic fruits, fruity smell, presence of Andean cereals and high alcoholic grade, and, based on these characteristics, a prototype of craft beer was developed. By using Napping®-UFP, consumers positioned and described the six samples of Peruvian craft beers (five commercial brands and the prototype), we found that the prototype developed showed floral smell, herbal odor, fruity smell, light golden color, bubbly, exotic fruits, and high alcoholic grade. The EPM showed that 80% of consumers scored the prototype with a high grade of taste. Finally, putting together these techniques turns out to be useful in obtaining products that are highly accepted by the consumer and this methodology could be applied to other products.